Tailored strategies for improved control of CAR-T cells in multiple myeloma - Bielowski, Anna; Kilian, Teresa; Vera-Cruz, Sarah; Deveuve, Quentin; Kraus, Sabrina; Einsele, Hermann; Hudecek, Michael; Danhof, Sophia (Frontiers in Immunology, 2026)
Recent advances in chimeric antigen receptor (CAR) T cell therapy have transformed the treatment landscape of multiple myeloma, yet almost all patients ultimately relapse. Chromosomal 1q gains are associated with a higher risk of disease progression and poor prognosis, suggesting that CAR-T targeting of chromosome 1–encoded antigens, such as SLAMF7, may be particularly relevant in advanced disease. However, novel CAR targets raise the risk of on-target, off-tumor toxicities, underscoring the need for controllable CAR-T systems. We systematically assessed pharmacologic and antibody-based strategies to modulate CD19- and SLAMF7-directed CAR-T cells. Tyrosine-kinase inhibitor dasatinib rapidly and reversibly inhibited CAR-T activation, serving as an efficient “on/off” switch with the limitation of also inhibiting unmodified T cells. To surpass this issue, we used antibody-dependent cell cytotoxicity to inhibit CAR-T cells. However, conditioning with fludarabine/cyclophosphamide profoundly depletes NK cells, limiting antibody-dependent CAR-T clearance in patients. Moreover, as NK cells express SLAMF7, they are susceptible to fratricidal cytotoxicity by SLAMF7 CAR-T cells, further reducing this potential off-switch mechanism. To bypass this immune effector cell dependence, we developed a novel strategy using antibody–drug conjugates (ADCs). In this work, we demonstrate that the BCMA-targeting ADC belantamab-mafodotin selectively eliminates BCMA co-expressing CAR-T cells without affecting unmodified T cells. These findings suggest ADCs as a potent, effector cell-independent safety mechanism for CAR-T therapies, potentially enhancing controllability and safety in future clinical applications.